Facile synthesis of a ZnO–BiOI p–n nano-heterojunction with excellent visible-light photocatalytic activity - Zhang, Mengyuan; Qin, Jiaqian; Yu, Pengfei; Zhang, Bing; Ma, Mingzhen; Zhang, Xinyu; Liu, Riping (Beilstein Journal of Nanotechnology, 2018)
In this paper, an efficient method to produce a ZnO/BiOI nano-heterojunction is developed by a facile solution method followed by calcination. By tuning the ratio of Zn/Bi, the morphology varies from nanoplates, flowers to nanoparticles. The heterojunction formed between ZnO and BiOI decreases the recombination rate of photogenerated carriers and enhances the photocatalytic activity of ZnO/BiOI composites. The obtained ZnO/BiOI heterostructured nanocomposites exhibit a significant improvement in the photodegradation of rhodamine B under visible light (λ ≥ 420 nm) irradiation as compared to single-phase ZnO and BiOI. A sample with a Zn/Bi ratio of 3:1 showed the highest photocatalytic activity (≈99.3% after 100 min irradiation). The photodegradation tests indicated that the ZnO/BiOI heterostructured nanocomposites not only exhibit remarkably enhanced and sustainable photocatalytic activity, but also show good recyclability. The excellent photocatalytic activity could be attributed to the high separation efficiency of the photoinduced electron–hole pairs as well as the high specific area.
Keywords: BiOI; photocatalytic degradation; p–n heterojunction; ZnO

(untitled) - Fujishiima, A.; Honda, K. (Nature, 1972)

(untitled) - Kumar, S.; Kumar, A.; Bahuguna, A.; Sharma, V.; Krishnan, V. (Beilstein J. Nanotechnol., 2017)

(untitled) - Zhang, X. Y.; Qin, J. Q.; Hao, R. R.; Wang, L. M.; Shen, X.; Yu, R. C.; Limpanart, S.; Ma, M. Z.; Liu, R. P. (J. Phys. Chem. C, 2015)

(untitled) - He, H. B.; Xue, S. S.; Wu, Z.; Yu, C. L.; Yang, K.; Peng, G. M.; Zhou, W. Q.; Li, D. H. (Chin. J. Catal., 2016)

(untitled) - Pathania, D.; Gupta, D.; Al-Muhtaseb, A. H.; Sharma, G.; Kumar, A.; Naushad, M.; Ahamad, T.; Alshehri, S. M. (J. Photochem. Photobiol., A, 2016)

(untitled) - Han, W. W.; Li, Z.; Li, Y.; Fan, X.; Zhang, F.; Zhang, G.; Peng, W. (Front. Chem. (Lausanne, Switz.), 2017)

(untitled) - Schrauzer, G. N.; Guth, T. D. (J. Am. Chem. Soc., 1977)

(untitled) - Chen, X. Z.; Li, N.; Kong, Z. Z.; Ong, W. J.; Zhao, X. J. (Mater. Horiz., 2018)

(untitled) - Tran, P. D.; Wong, L. H.; Barber, J.; Loo, J. S. C. (Energy Environ. Sci., 2012)

(untitled) - Saravanan, R.; Shankar, H.; Prakash, T.; Narayanan, V.; Stephen, A. (Mater. Chem. Phys., 2011)

(untitled) - Pathania, D.; Katwal, R.; Sharma, G.; Naushad, M.; Khan, M. R.; Al-Muhtaseb, A. H. (Int. J. Biol. Macromol., 2016)

(untitled) - Pandiyarajan, T.; Saravanan, R.; Karthikeyan, B.; Gracia, F.; Mansilla, H. D.; Gracia-Pinilla, M. A.; Mangalaraja, R. V. (J. Mater. Sci.: Mater. Electron., 2017)

(untitled) - Gnanasekaran, L.; Hemamalini, R.; Saravanan, R.; Ravichandran, K.; Gracia, F.; Agarwal, S.; Gupta, V. K. (J. Photochem. Photobiol., B, 2017)

Chemistry for Sustainable Develoment - Novokreshchenova, M. N.; Yukhin, Y.; Bokhonov, B. B. (Springer, 2005)

(untitled) - Chen, X. B.; Mao, S. S. (Chem. Rev., 2007)

(untitled) - Yu, J. G.; Yu, X. X. (Environ. Sci. Technol., 2008)

(untitled) - Yu, C. L.; Zhou, W. Q.; Zhu, L. H.; Li, G.; Yang, K.; Jin, R. C. (Appl. Catal., B: Environ., 2016)

(untitled) - Kudo, A.; Omori, K.; Kato, H. (J. Am. Chem. Soc., 1999)

(untitled) - Zhao, X.; Chen, Z. (Beilstein J. Nanotechnol., 2017)

(untitled) - Tang, J. W.; Zou, Z. G.; Ye, J. H. (Catal. Lett., 2004)

(untitled) - Tang, J. W.; Zou, Z. G.; Ye, J. H. (Angew. Chem., Int. Ed., 2004)

(untitled) - Yu, C. L.; Wu, Z.; Liu, R. Y.; Dionysiou, D. D.; Yang, K.; Wang, C. Y.; Liu, H. (Appl. Catal., B: Environ., 2017)

(untitled) - Xiao, X.; Zhang, W. D. (J. Mater. Chem., 2010)

(untitled) - An, H. Z.; Du, Y.; Wang, T. M.; Wang, C.; Hao, W. C.; Zhang, J. Y. (Rare Met., 2008)

(untitled) - Huang, W. L. (J. Comput. Chem., 2009)

(untitled) - Yu, C. L.; Zhou, W. Q.; Yu, J. C.; Liu, H.; Wei, L. F. (Chin. J. Catal., 2014)

(untitled) - Qin, J. Q.; Yang, C. W.; Cao, M.; Zhang, X. Y.; Rajendran, S.; Limpanart, S.; Ma, M. Z.; Liu, R. P. (Mater. Lett., 2017)

(untitled) - Ong, W. J. (Front. Mater., 2017)

(untitled) - Zeng, D. Q.; Xiao, L.; Ong, W. J.; Wu, P. Y.; Zheng, H. F.; Chen, Y. Z.; Peng, D. L. (ChemSusChem, 2017)

(untitled) - Lv, C. D.; Chen, G.; Zhou, X.; Zhang, C. M.; Wang, Z. K.; Zhao, B. R.; Li, D. Y. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Zhang, K. H. L.; Rui, W.; Tang, F.; Li, W.; Oropeza, F. E.; Liang, Q.; Lazarov, V. K.; Du, Y.; Payne, D. J.; MacManus-Driscoll, J. L.; Blamire, M. G. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Zhang, X.; Zhang, L. Z.; Xie, T. F.; Wang, D. J. (J. Phys. Chem. C, 2009)

(untitled) - Jiang, J.; Zhang, X.; Sun, P. B.; Zhang, L. Z. (J. Phys. Chem. C, 2011)

(untitled) - Yu, Y. X.; Ouyang, W. X.; Zhang, W. D. (J. Solid State Electrochem., 2014)

(untitled) - Kuang, P.-Y.; Ran, J.-R.; Liu, Z.-Q.; Wang, H.-J.; Li, N.; Su, Y.-Z.; Jin, Y.-G.; Qiao, S.-Z. (Chem. – Eur. J., 2015)

(untitled) - Tong, Y. H.; Zheng, C.; Lang, W. J.; Wu, F.; Wu, T.; Luo, W. Q.; Chen, H. F. (Mater. Des., 2017)

(untitled) - Jiang, J. J.; Wang, H. T.; Chen, X. D.; Li, S.; Xie, T. F.; Wang, D. J.; Lin, Y. H. (J. Colloid Interface Sci., 2017)

(untitled) - Al-Gaashani, R.; Radiman, S.; Daud, A. R.; Tabet, N.; Al-Douri, Y. (Ceram. Int., 2013)

(untitled) - Reddy, K. H.; Martha, S.; Parida, K. M. (Inorg. Chem., 2013)

(untitled) - Sing, K. S. W.; Everett, D. H.; Haul, R. A.; Moscou, L.; Pierotti, R. A.; Rouquérol, J.; Siemieniewska, T. (Pure Appl. Chem., 1985)

(untitled) - Dimitrov, V.; Komatsu, T. (J. Solid State Chem., 2002)

(untitled) - Sun, J. J.; Li, X. Y.; Zhao, Q. D.; Tadé, M. O.; Liu, S. M. (Appl. Catal., B: Environ., 2017)

(untitled) - Zhang, X.; Qin, J.; Xue, Y.; Yu, P.; Zhang, B.; Wang, L.; Liu, R. (Sci. Rep., 2014)

(untitled) - Gurunathan, K. (Int. J. Hydrogen Energy, 2004)

(untitled) - Sambandam, B.; Surenjan, A.; Philip, L.; Pradeep, T. (ACS Sustainable Chem. Eng., 2015)

(untitled) - Ye, L. Q.; Tian, L. H.; Peng, T. Y.; Zan, L. (J. Mater. Chem., 2011)

(untitled) - Jing, L. Q.; Xu, Z. L.; Shang, J.; Sun, X. J.; Cai, W. M.; Guo, H. C. (Mater. Sci. Eng., A, 2002)

(untitled) - Zhang, Z. Y.; Shao, C. L.; Li, X. H.; Wang, C. H.; Zhang, M. Y.; Liu, Y. C. (ACS Appl. Mater. Interfaces, 2010)

(untitled) - Wang, Y.; Fang, H. B.; Ye, R. Q.; Zheng, Y. Z.; Li, N.; Tao, X. (RSC Adv., 2016)

(untitled) - Ansari, S. A.; Khan, M. M.; Kalathil, S.; Nisar, A.; Lee, J.; Cho, M. H. (Nanoscale, 2013)

(untitled) - Tauc, J. (Mater. Res. Bull., 1968)

(untitled) - Davis, E. A.; Mott, N. F. (Philos. Mag., 1970)

(untitled) - Wang, L.; Ouyang, S.; Ren, B.; Ye, J.; Wang, D. (APL Mater., 2015)

(untitled) - Li, T. B.; Chen, G.; Zhou, C.; Shen, Z. Y.; Jin, R. C.; Sun, J. X. (Dalton Trans., 2011)

(untitled) - Liu, Y. F.; Yao, W. Q.; Liu, D.; Zong, R. L.; Zhang, M.; Ma, X. G.; Zhu, Y. F. (Appl. Catal., B: Environ., 2015)

(untitled) - Yoon, H. J.; Choi, Y. I.; Jang, E. S.; Sohn, Y. (J. Ind. Eng. Chem., 2015)

(untitled) - Yu, C. L.; Fan, C. F.; Yu, J. C.; Zhou, W. Q.; Yang, K. (Mater. Res. Bull., 2011)